Pengaruh Ekstrak Etanolik Atau Ekstrak Dekok Ganoderma Lucidum (ß Glucan) Terhadap Hormon Testosteron, Sel Leidiq Testis Rattus Norvegicus Jantan. - Bambang Wasito Tjipto (JURNAL WIDYA MEDIKA, 2019)
The process of "aging" causes a decline in physical and mental strength. In general, more and more bodily organs are complained of by elderly people, and suffer from chrnic diseases. Older men experience various changes including a decrease in endocrine, cardiovascular, neurological, eye, skin, reproductive and so on. The Late Onset Hypogonadism (LOH) is a syndrome that decreases sexual, physical, and psychological abilities associated with a decrease in testosterone levels in the blood. In middle age, the age of 45-59 years begins to decrease body function, including decreased reproductive function and the function of sexuality, hormones such as testosterone. which is known as aging process. Testosterone is an anabolic hormone. Giving Ganoderma Lucidum in a preliminary study of normal one-year-old male Rattus norvegicus rats, water extract (dekok) and ethanol extract with different doses, 10 mg / kg, 20 mg / kg bw, and 30 mg kg / bb proved to increase total testosterone hormone serum significantly at a dose of 30 mg / kg bw, then researchers increase the dose to 50 mg / kg bw. Purpose of the study: Analyzing the effect of dekok extract or Ganoderma lucidum ethanolic extract on the hormone testosterone, testicular Leidiq cells that are undergoing the aging process. Results: Test profile of testosterone, after administration between controls, extract of dekok and male ethanol extract of 18 months old male Leydig Rattus norvegicus testis. In different tests on testosterone, there were significant differences between controls, dekok extract and ethanol extract. The results of testosterone levels in ethanol extract were higher. Conclusion: Dekok and Ganoderm lucidum ethanol extract can increase testosterone hormone